Penerapan Prinsip Hakim Pasif dan Aktif dalam Proses Pembuktian Hukum Acara Perdata - Ayu Afrilia, Niken; Ahlakul Karimah, Latifah; Widiasari, Pipit; Zora Rafi’, Berlian (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The quality and fairness of the decisions made are greatly influenced by the role of the judge in the process of evidence in civil procedural law. This article discusses the application of active and passive judge principles in the evidentiary process and their implications for civil rulings. The issues raised include how judges play a role in applying both principles and how this affects the quality and fairness of their decisions. The research method used is normative juridical or doctrinal research, which emphasizes the analysis of relevant legal norms. The results of the discussion indicate that judges must be able to balance their active and passive roles in various stages of the trial, including mediation, providing advice and assistance, the questioning stage, evidence presentation, and the pronouncement of verdicts. The application of active and passive judge principles appropriately has been proven to positively influence the achievement of substantive justice in civil rulings. Therefore, a deep understanding of these two principles is essential for judges in their efforts to achieve fair and effective justice.